Brief report: association between autism spectrum disorder, gastrointestinal problems and perinatal risk factors within sibling pairs - Isaksson, Johan; Bölte, Sven (Journal of autism and developmental disorders, 2017)
Autism spectrum disorder (ASD) has been associated with gastrointestinal (GI) problems, but the nature of this association is unclear. Parents to siblings, concordant or discordant for ASD (N = 217), participated in a web survey covering mother’s weight gain during pregnancy, maternal viral/bacterial infection and use of antibiotics, duration of breastfeeding, mode of delivery, birth weight and child GI problems. ASD was associated with GI problems and perinatal environmental risk, based on a summation of maternal infection and antibiotic use during pregnancy and/or the breastfeeding period. The association between GI problems and ASD remained within the sibling pairs (β = 1.23; p < .001) in the adjusted model. Our results indicate non-shared environmental effects on the ASD/GI association, but none of the factors examined explained the link.